2021
DOI: 10.1002/jeq2.20210
|View full text |Cite
|
Sign up to set email alerts
|

Variability in fluvial suspended and streambed sediment phosphorus fractions among small agricultural streams

Abstract: Agriculture is a major source of sediment and particulate phosphorus (P) inputs to freshwaters. Distinguishing between P fractions in sediment can aid in understanding its eutrophication risk. Although streams and rivers are important parts of the P cycle in agricultural catchments, streambed sediment and especially fluvial suspended sediment (FSS) and its P fractions are less studied. To address this knowledge gap, seasonal variations in FSS P fractions and their relation to water quality and streambed sedime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 65 publications
(105 reference statements)
0
0
0
Order By: Relevance
“…The range of TP content in channel bed sediments was consistent with other agricultural streams in Sweden (0.07-1.57 g P kg −1 , Lannergård et al, 2020; 0.35-1.85 g P kg −1 , Sandström et al, 2021), indicating that remediated streams do not promote P enrichment in channel beds compared with streams without floodplains. However, the proportions of labile P fractions were overall lower in our study, either explained by less deposition of these fractions or a more rapid turnover of labile P. In a comparable system, sediments were also dominated by recalcitrant fractions that were shown to be stable over seasons (Kindervater and Steinman, 2019).…”
Section: Variability In Sediment P Stocksupporting
confidence: 82%
See 1 more Smart Citation
“…The range of TP content in channel bed sediments was consistent with other agricultural streams in Sweden (0.07-1.57 g P kg −1 , Lannergård et al, 2020; 0.35-1.85 g P kg −1 , Sandström et al, 2021), indicating that remediated streams do not promote P enrichment in channel beds compared with streams without floodplains. However, the proportions of labile P fractions were overall lower in our study, either explained by less deposition of these fractions or a more rapid turnover of labile P. In a comparable system, sediments were also dominated by recalcitrant fractions that were shown to be stable over seasons (Kindervater and Steinman, 2019).…”
Section: Variability In Sediment P Stocksupporting
confidence: 82%
“…Internal erosion from trapezoidal channels can therefore contribute with higher sediment and P loads compared with distal sediment sources in catchments (Simon and Rinaldi, 2006). Closely interlinked with sediment conveyance in channels is the instream transport and storage of P, governed by fluvial processes (deposition/resuspension of sediment-bound P; Ballantine et al, 2009;Noe et al, 2019), redox processes (adsorption/desorption of soluble reactive P [SRP] to SS; Sandström et al, 2021) and geomorphic stability (streambank erosion;Fox et al, 2016). Channel bed sediments can store high amounts of P (Ballantine et al, 2009) and although deposition has been found to dominate in headwater reaches owing to stream power limitation (Worrall et al, 2020), sediment-bound P becomes susceptible to remobilization during high flow events (Bowes et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The lack of TP load response to a reduction in phosphorus fertilisation corresponded with results by Capell et al (2021) in the Baltic sea region, but contrasted with the outcomes from Ockenden et al (2017) in England. The strong binding of phosphate to finetextured soils and sediments in the study sites might form an explanation (Sandström et al, 2021).…”
Section: Mitigating Future Nutrient Loads In Light Of Eu Green Deal T...mentioning
confidence: 92%
“…Agricultural production efforts generate large volumes of rainfall-runoff derived from farmlands that (Leng et al, 2021), owing to the excessive application of chemical fertilizers and pesticides, carry large amounts of nitrogen (N) that can cause serious surface water pollution (Butkovskyi et al, 2021). Nutrient levels in surface bodies of water that are derived from such receding farmland water runoff can rise as high as 60%-80% (Hu, Yang, Han and Wang, 2019), making these waters the primary non-point source of agriculture-associated pollution (Lavrnić et al, 2018;Jabbar and Grote, 2019;Kaandorp et al, 2021;Sandström et al, 2021). China is a large nation with an extensive agricultural system that relies on the use of large quantities of chemical fertilizers, posing a major risk to Chinese surface water quality owing to the potential for farmland-derived runoff pollution.…”
Section: Introductionmentioning
confidence: 99%